Potencial nematófago de espécies de Hohenbuehelia spp. e de Trichoderma koningiopsis sobre Meloidogyne javanica na cultura do feijoeiro cv. IPR Uirapuru - Lubian, Cleonice (2019)
Nematoses controlling strategies are limited and there are demand for alternative biological products. Trichoderma genus has been widely explored but for Hohenbuehelia researches are rare for nematode management. The main aim was to evaluate nematophagous potential of H. mastrucata, H. barbatula, H. bullulifera, H. portegna, H. petaloides, H. paraguayensis and T. koningiopsis against M. javanica in bean crop Cv. IPR Uirapuru, in greenhouse. It was evaluated number of galls and eggs masses on root in three root regions: basal, intermediate and tip; nematode reproduction factor (RF); vegetal development parameters (plants height on V1, V2, V4 and R5 growth stages, root length, aerial part and root dry weight); inoculum dose and the best preparation technique. Treatments were composed by individual interaction of each fungal isolate with 4000 eggs of M. javanica, having a total control (bean) and a partial control (bean + nematode) arranged in completely randomized design with four repetitions. Data were tested by Scott-Knott (5%). The dose of 0,23 g of colonized rice enabled fungi permanency in substrate, being better colonized by fungal addition to rice than the opposite. Only dry weight of roots had significant difference, mainly for H. mastrucata, H. portegna and H. paraguayensis. Higher egg mass reductions were through H. mastrucata, H. portegna and H. petaloides, and for galls, by all Hohenbuehelia species. For both parameters there was control at basal portion not being evident to the others root portions. For egg counting on root, H. mastrucata highlighted with RF of 0.4, followed by H. portegna (0.76), H. paraguayensis (0.96) and H. petaloides (1.03).